The great puppypalooza - Ecton, Emily (Ecton, Emily, Great Pet Heist, 2025)
Butterbean rescues a puppy cornered by the nefarious Animal Control Man, but when that one puppy turns out to be a whole pack, it becomes up to her and her gang of super spy and ghost hunting friends to find these puppies new homes.